Estudio de mejora en el aprovisionamiento y la gestión de almacenes de la empresa Tuesta Consultores y Ejecutores E.I.R.L. - Cueva Mori, Cynthia Graciela (2022)
The objective of this work is to carry out and implement a study to improve the procurement process and warehouse management of the company Tuesta Consultores y Ejecutores E.I.R.L. This study is developed within the logistics area of the company, which is located in the district and province of Chachapoyas, in the Amazon region, Perú, dedicated to carry out building, sanitation and road works for the public sector. Likewise, the sector in which the company operates was analyzed through Porter's five forces. The specific objectives were established to achieve the general objective, for which the DMAIC (define, measure, analyze, implement and control) methodology was used, defining the problem that affects procurement and warehouse management, establishing indicators (cost overrun index, requirements attention time index, on-time requirements index, purchase order attention index, inventory coverage) that will measure the current baseline and the future one after the implementation of the improvement study. To do this, the causes of the problem were analyzed, prioritizing them in order to determine solutions and improve procurement and warehouse management, developing a series of measures to mitigate the prioritized causes, with the aim to improve the established indicators. Finally, the indicators were evaluated to determine the benefit of the study to the logistics area of the company in its procurement and warehouse management process; likewise, the benefit-cost of the implementation of the improvement study was determined.